The Neandertal vertebral column 2: The lumbar spine. Issue 106 (May 2017) - Gómez-Olivencia, Asier; Arlegi, Mikel; Barash, Alon; Stock, Jay T.; Been, Ella
Abstract: Here we provide the most extensive metric and morphological analysis performed to date on the Neandertal lumbar spine. Neandertal lumbar vertebrae show differences from modern humans in both the vertebral body and in the neural arch, although not all Neandertal lumbar vertebrae differ from modern humans in the same way. Differences in the vertebral foramen are restricted to the lowermost lumbar vertebrae (L4 and L5), differences in the orientation of the upper articular facets appear in the uppermost lumbar vertebrae (probably in L1 and L2–L3), and differences in the horizontal angle of the transverse process appear in L2–L4. Neandertals, when compared to modern humans, show a smaller degree of lumbar lordosis. Based on a still limited fossil sample, early hominins (australopiths and Homo erectus ) had a lumbar lordosis that was similar to but below the mean of modern humans. Here, we hypothesize that from this ancestral degree of lumbar lordosis, the Neandertal lineage decreased their lumbar lordosis and Homo sapiens slightly increased theirs. From a postural point of view, the lower degree of lordosis is related to a more vertical position of the sacrum, which is also positioned more ventrally with respect to the dorsal end of the pelvis. This results in a spino-pelvic alignment that, though different from modern humans, maintained an economic postural equilibrium. Some features, such as a lower degree of lumbar lordosis, were already present in the middle Pleistocene populations ancestral to Neandertals. However, these middle Pleistocene populations do not show the full suite of Neandertal lumbar morphologies, which probably means that the characteristic features of the Neandertal lumbar spine did not arise all at once.